2021
DOI: 10.1007/s00122-021-03953-5
|View full text |Cite
|
Sign up to set email alerts
|

Pinpointing genomic regions associated with root system architecture in rice through an integrative meta-analysis approach

Abstract: Applying an integrated meta-analysis approach lead to identification of meta-QTLs/ candidate genes associated with rice root system architecture, which can be used in MQTL-assisted breeding/ genetic engineering of root traits.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 151 publications
0
18
0
Order By: Relevance
“…A meta-analysis study of root traits, based on 128 published studies under field conditions, has shown that drought significantly decreased root length and root length density, while it increased root diameter and root-to-shoot biomass ratio (Zhou et al, 2018). A wholegenome meta-analysis was performed to find out candidate genes and genomic regions involved in controlling RSA traits under well-watered and drought stress conditions in rice (Daryani et al, 2022) and other major cereal crops including maize (Guo et al, 2018), bread wheat (Darzi-Ramandi et al, 2017;Soriano and Alvaro, 2019;Bilgrami et al, 2020), and durum wheat (Iannucci et al, 2017). Specifically, plant hormones are known to play critical roles in the molecular regulation of RSA traits under drought and the progress has been reviewed by Ranjan et al (2022).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis study of root traits, based on 128 published studies under field conditions, has shown that drought significantly decreased root length and root length density, while it increased root diameter and root-to-shoot biomass ratio (Zhou et al, 2018). A wholegenome meta-analysis was performed to find out candidate genes and genomic regions involved in controlling RSA traits under well-watered and drought stress conditions in rice (Daryani et al, 2022) and other major cereal crops including maize (Guo et al, 2018), bread wheat (Darzi-Ramandi et al, 2017;Soriano and Alvaro, 2019;Bilgrami et al, 2020), and durum wheat (Iannucci et al, 2017). Specifically, plant hormones are known to play critical roles in the molecular regulation of RSA traits under drought and the progress has been reviewed by Ranjan et al (2022).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-QTL (MQTL) analysis is a good integrated method. It had been used to estimate the CI of many traits of QTL in many crops [ 17 20 ]. In 2012, Sala et al summarized 184 QTLs related GWC and performed MQTL analysis on GWC of maize, 34 MQTLs related to GWC were obtained [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, 20 ortho-MQTLs were conserved between maize and rice genomes. Among the 20 ortho-MQTLs, 7 MQTLs (viz., MQTL 2.2, 2.5, 4.5, 4.7, 7.2, and 7.7) were verified by the rice root meta-QTL studies [ 35 , 36 ]. Such conserved ortho-MQTLs suggest the presence of some common regulatory elements that govern the functions of many root-related genes [ 35 , 42 ].…”
Section: Discussionmentioning
confidence: 88%
“…In the present study, 52.9% of MQTLs (36 out of 68) were validated using GWAS-MTAs obtained from ten maize root GWA studies. Such a comparison of the MQTLs with GWAS-based MTAs has been performed in a few earlier studies in maize [ 28 , 32 , 35 , 36 ]. These 36 MQTLs co-localized with MTAs associated with different traits, including root angle, diameter, length, number, area, and root weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation